Assessing the Readiness of School Principals for Digital Leadership: An Exploratory Data Analysis Approach - Suryaman, Maman; Setiyani, Lila (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The growing demand for quality education in the digital era requires schools to adopt strategic and visionary leadership, particularly in integrating digital technologies. This study investigates the readiness of school principals in implementing digital leadership by examining key dimensions, including visionary leadership, digital-age learning culture, professional development, systemic improvement, ethical technology use, and strategic resource planning. Employing a quantitative descriptive approach, the study uses Exploratory Data Analysis (EDA) to uncover patterns and relationships across multiple indicators of digital leadership. Data was collected through structured questionnaires distributed to 43 vocational school leaders in Karawang Regency, Indonesia, during a facilitated community engagement programme. The findings reveal that professional development is the most influential factor in supporting digital leadership readiness, followed closely by systemic improvement and the cultivation of a digital-age learning culture. Additionally, strategic partnerships, ethical use of technology, and the provision of infrastructure and equitable digital access are strongly interconnected, highlighting the need for a holistic approach to digital leadership. Visionary leadership, while important, shows relatively lower correlation, suggesting that vision alone is insufficient without operational and developmental support. This study concludes that digital leadership readiness is not the result of isolated efforts but the outcome of a comprehensive and coordinated strategy involving human resource capacity, institutional culture, infrastructure, and ethical guidance.